Organization of Independent Work of Higher Education Students - Hamidova Madinabonu Abduboriyevna (Researchparks Publishing, 2022)
The article describes the process of organization of independent work of higher education students. Independent work is not an end in itself. It is a means of fighting for deep and solid knowledge of students, a means of forming their activity and independence as personality traits, and developing their mental abilities. The organization of independent work, its management is a responsible and complex work of every teacher. The upbringing of activity and independence must be considered as an integral part of the developing students’ abilities. This task appears before every teacher among the tasks of basic importance.